Politically Motivated Extreme-Right Attacks Against Elected Representatives in Contemporary Germany - Kałabunowska, Agata (Perspectives on terrorism, 2022)
The discovery of the NSU terrorist cell, the Halle synagogue shooting, and the murder of nine persons with a migration background in Hanau caused a serious shift in the perception of the extreme right in Germany and led to a number of legislative changes. The killing of CDU politician Walter Lübcke by a sympathiser of the far right should be considered a negative highlight that drew attention to the security of elected representatives. This article offers an overview of available official data on the scale of the threat by the extreme right in Germany in general and on violent attacks against public figures, including elected representatives, in particular. It analyses three instances of attacks against politicians (Henriette Reker, Andreas Hollstein and Walter Lübcke) and discusses as well a series of threats from the so-called NSU 2.0, the aim being to discover underlying patterns of violence. The author also briefly reviews countermeasures taken by the federal government in order to prevent and counter far-right threats in the Germany of today.